2016
DOI: 10.1016/j.phrs.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Friend or foe? Telomerase as a pharmacological target in cancer and cardiovascular disease

Abstract: Aging, cancer, and chronic disease have remained at the forefront of basic biological research for decades. Within this context, significant attention has been paid to the role of telomerase, the enzyme responsible for lengthening telomeres, the nucleotide sequences located at the end of chromosomes found in the nucleus. Alterations in telomere length and telomerase activity are a common denominator to the underlying pathology of these diseases. While nuclear-specific, telomere-lengthening effects of telomeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 105 publications
0
23
0
Order By: Relevance
“…In translating these findings, it will be important to consider the effects of upregulating telomerase in noncardiac diseases. For example, although not an oncogene, TERT is involved in support of tumor growth and metastasis (1). The risk versus benefit of TERT activation or inhibition needs to be carefully considered in different cell types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In translating these findings, it will be important to consider the effects of upregulating telomerase in noncardiac diseases. For example, although not an oncogene, TERT is involved in support of tumor growth and metastasis (1). The risk versus benefit of TERT activation or inhibition needs to be carefully considered in different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…The risk versus benefit of TERT activation or inhibition needs to be carefully considered in different cell types. Current evidence indicates that the proliferative functions of TERT are driven by its canonical telomere nuclear lengthening effects (1). Separating mitochondrial and nuclear actions of telomerase would help advance further discovery in this field.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the nuclear and nucleolar localization, telomerase also attains cytoplasmic and mitochondrial localizations, which have strong implications with cardiovascular diseases. It is known that hTERT contains a N-terminal mitochondrial targeting sequence, which is crucial for its mitochondrial translocation [ 45 , 46 ]. Beyer et al [ 37 ] have demonstrated that hTERT shuttles directly to the mitochondria under oxidative stress, a characteristic of cardiovascular disease [ 47 ].…”
Section: Emerging Roles Of Telomerasementioning
confidence: 99%
“…There are reports about the use of telomerase as a therapeutic tissue-specific target for diseases of the cardiovascular system [61,62]. Telomerase can be used to treat coronary heart disease due to protection against ROS [63,64]. With ischemia reperfusion injury, telomerase deficiency leads to heart failure [65].…”
Section: Heart Agingmentioning
confidence: 99%